DementiaCare: A Dementia Health Monitoring System - AZMI, RABIATUL ADAWIYAH; MAT REJAB, MAZIDAH (Applied Information Technology And Computer Science, 2025)
Dementia is an escalating global health concern, affecting millions worldwide and placing significant strain on both patients and caregivers. This study introduces DementiaCare, a web-based health monitoring system designed to enhance dementia management by promoting patient independence and improving caregiver efficiency at Hayati Care Centre. The system features a responsive mobile-friendly interface accessible via standard web browsers, ensuring accessibility across devices without the need for a native app. Developed using programming principles and powered by a MySQL database, DementiaCare supports real-time data tracking, routine management, and streamlined communication among stakeholders. Utilizing the Waterfall software development model, the system emphasizes modularity, user-friendliness, and secure data handling. Findings indicate that DementiaCare improves adherence to care routines, enhances data accuracy, and reduces caregiver workload compared to traditional manual methods. Future work should explore expanding the system’s capabilities to include predictive analytics and broader adaptability across diverse healthcare settings.